Partnership Cooperation Models in Fiqh Muamalah: A Case Study of Kencana Mulia Sejahtera Cooperative in Ngawi - Imam, Imam kamaluddin; Eko, Eko Nur Cahyo; Daniswara, Aliyya Lathifa Daniswara; Muqorobin, Ahmad (Islamic Economics Journal, 2025)
This study aims to analyse the partnership pattern applied by Kencana Mulia Sejahtera Cooperative in Ngawi in the perspective of fiqh muamalah. This cooperative focuses on a form of cooperation between cooperatives and their members, aiming to increase coffee production and sales. Using a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation, then processed through data reduction, data display, and conclusion drawing. The findings show that the partnership implemented by Kencana Mulia Sejahtera Cooperative and its members follows two partnership patterns. When examined through the lens of fiqh muamalah, these partnership patterns align with syirkah ‘inan and mudharabah. The profit-sharing mechanism is based on each party’s contribution, with risks shared proportionally. The analysis shows that the partnership reflects syirkah ‘inan, where both contribute capital and share profits, and mudharabah, where the cooperative manages farmers’ capital for marketing. This structured cooperation mechanism has strengthened the economic position of farmers by ensuring fair distribution, price stability, and access to a broader market. Further research is recommended to refine the implementation of this partnership model in other agribusiness sectors and improve its operational efficiency.